Testicular cancer in three brothers. Issue 767 (September 1989) - Raina, V.; Young, P. T.; Soukop, M.
Abstract : Three of four brothers in a family were diagnosed to have testicular tumour. All brothers were in their twenties at diagnosis and all had malignant teratoma, intermediate. One of the brothers, in addition, had a seminoma on the same side as the teratoma. The cases were unusual as there was no family history of cancer and no congenital abnormalities, such as cryptorchidism. Chromosomal analysis and HLA typing did not help in elucidating the cause of this rare familial occurrence of testicular tumour.